A Novel Protection Design Process to Increase Microgrid Resilience - Vygoder, Mark; Banihashemi, Farzad; Gudex, Jacob; Eggebeen, Andrew; Oriti, Giovanna; Cuzner, Robert M. (IEEE transactions on industry applications, 2024)
Successful discrimination of, isolation from, and recovery against short-circuit electrical faults within microgrids having distributed energy resources (DERs) is challenging, as protection coordination must include not only the distribution equipment, but also control and low voltage ride-through settings of DERs. This is especially the case when grid resilience is improved by use of the microgrid to maintain services from DERs (localized to an installation) following utility grid outages. Under islanded configurations, continued reliability of power delivery is essential, even in the face of subsequent electrical faults. The main purpose of this paper is to propose a novel protection design process, and to demonstrate it on an islanded ac microgrid with parallel feeders. The contribution is a methodology for coordinated circuit breaker protection and ride-through settings, thereby maximizing the post-fault recoverability of an ac microgrid subject to faults in an islanded configuration. The aim is improve the microgrid resilience in islanded configurations. The protection and IEEE Standard 1547-2018 ride-through settings are validated in controller hardware-in-the-loop simulation, validating the proposed design process. Additionally, detailed implementation of ride-through enabling controls are discussed.